Person-centred therapy in the management of pre-retirement anxiety among federal road safety officers in Edo State, Nigeria (2024)
Pre-retirement anxiety is a challenge facing about to retire officers. It is a state of fear and uneasiness from active work-life is associated with the Federal Road Safety (FRS) officers. Past studies on pre-retirement anxiety among FRS officers concentrated on causal factors with little intervention studies. This study, therefore, investigated the challenges of pre-retirement anxiety within the context of FRS officers in Edo zone comprising Anambra, Delta and Edo states, Nigeria, with cognisant of their occupational stressors, cultural factors and individual experiences. The study was anchored to continuity theory of retirement, while a mixed methods approach was employed to access anxiety levels and psychological wellbeing as well as qualitative interviews to explore the experiences and perceptions of some of the officers undergoing therapy. Purposive sampling was used in selecting the 30 retiring participants (less than five years) into the groups. Participants with 60% and above score on retirement anxiety screening tool with their consent were used in the study. The instruments used were Pre-retirement Anxiety (α=.90) and Social-support (α =.70) scales. Hypotheses were raised and tested. Data were analysed using analysis of Covariance and Scheffe Post-hoc test @ 0.05 level of significance. Results revealed the effectiveness of PCT in managing pre-retirement anxiety of the officers. There was no interaction effect of treatment, gender and social support on pre-retirement anxiety of the officers. Person-centred therapy was effective in managing pre-retirement anxiety among FRS officers. Counseling psychologists should adopt this intervention when handling issues related to pre-retirement anxiety.